Does qualitative viral load testing shorten the window period for diagnosing HIV in individuals attending for post-exposure prophylaxis?. (August 2020) - Whitlock, Gary; Nwokolo, Nneka; ,
A fourth-generation HIV test is conventionally performed at baseline for individuals given HIV post-exposure prophylaxis (PEP). However, early HIV infection may be missed by fourth-generation tests especially in settings of high HIV incidence, meaning that recently infected individuals are potentially at risk of transmitting HIV. In 2013, HIV incidence in PEP recipients at the 56 Dean Street clinic was 7.6 per 100 person-years. We therefore wished to see if using a point-of-care PCR HIV test in such individuals would shorten the testing window period and pick up early infections that would be undiagnosed by conventional tests. We compared HIV detection in PEP recipients using the Cepheid GeneXpert® HIV-1 Qual viral load (Qual VL) assay with the standard HIV tests used in our clinical service. Between March 2017 and August 2018, a Qual VL assay was performed in addition to standard baseline HIV tests in consented PEP recipients. Of 494 consented PEP recipients, 476 had valid Qual VL assay results. Of these, 474 (99.6%) had a negative Qual VL result and were also negative on standard baseline HIV tests. Two (0.4%) tested positive for HIV on Qual VL. One of these patients was also HIV-positive on all baseline HIV tests. The other had discordant baseline point-of-care HIV test results. Although no additional HIV infections were diagnosed in PEP recipients using Qual VL, in one individual, it provided confirmation of new HIV infection more quickly than the standard HIV testing pathway.